Implementation Sequence Optimization for Dedicated Bus Lane Projects. Issue 10 (October 2021) - Bayrak, Murat; Guler, S. Ilgin; Schonfeld, Paul
Transportation projects are often implemented in phases, and the total project duration can span years. Optimization of the sequence in which transportation projects are implemented can decrease the severity of disruptions caused by construction, reduce the total cost of projects, and increase the present value of the benefits of the project. This paper presents a method for optimizing the sequence and location of dedicated bus lane implementations. The proposed method is based on a bi-level optimization framework. The lower level simulates the traffic using a link transmission model to evaluate car and bus delays, while the upper level optimizes the locations of bus lanes and/or the implementation sequence of a given bus lane configuration. If the budget or other resource constraints are binding, the optimized sequence uniquely determines the optimal schedule. The solution method is evaluated for a test network, and an analysis of sensitivity to different demand patterns and different bus lane configurations is conducted. First, the optimized locations for bus lane implementation are determined for an illustrative test network. Results suggest that, when considering the implementation sequence for the optimized set of bus lane locations, the sequence of implementation does not yield significant benefits. However, if bus lanes are implemented on every possible link, the results suggest that prioritizing the implementation of bus lanes on peripheral links would reduce the total cost the most. These locations coincide with the set of optimized locations for bus lane implementation. Further tests considering non-uniform demand patterns also confirm these findings.